Fetal giant right cervical cyst causing severe tracheal compression: A case report. Issue 31 (August 2019) - Kang, Yanming; Ma, Yushan; Jiang, Xiaoqin; Lin, Xuemei; Zhao, Fumin
Abstract: Rationale: Fetal giant cervical cyst (FGCC) is a rare congenital anomaly. Sometimes FGCC may extend into the mediastinum, and result in severe tracheal compression, which is a life-threatening event at birth. Patient concerns: We present a rare case of FGCC, which extended from the right neck into the superior mediastinum, and resulted in severe tracheal compression. Diagnoses: An FGCC was observed by ultrasonography and magnetic resonance imaging (MRI) at 27+4 weeks' gestation (WG). Fetal MRI at 35+1 WG showed that the FGCC was 3.3 × 8.2 × 7.5 cm and extended from the right neck into the superior mediastinum. Severe tracheal compression was observed and the inside diameter of the narrowest section of tracheostenosis appeared thread-like and measured only 0.1 cm. Interventions: Cervical cyst reduction was performed prenatally under ultrasound guidance to alleviate the tracheal compression and maximize the chance of fetal survival 2 days before birth. At 36+3 WG, cesarean section was performed, and a female neonate was immediately delivered and intubated (3.5-mm tube) by an experienced anesthesiologist. Neonatal intralesional sclerotherapy and cystic component aspiration as guided by digital subtraction angiography were performed under general anesthesia. Anesthesia was maintained only with sevoflurane 3% in 2 L/min oxygen. Extubation was performed soon after surgery. Outcome: The neonate recovered uneventfully and was discharged 2 days postoperatively. After 140 days of follow-up, the neonate had recovered completely. Lessons: If an FGCC is suspected by abdominal ultrasound, a fetal MRI is recommended to assess the severity of tracheal compression before birth, if feasible. An anesthesiologist should assess the risk of intubation failure at birth according to those results. If fetal severe tracheal compression is detected and it may result in inability of intubation at birth, prenatal cervical cyst reduction under ultrasound guidance may be effective for alleviating tracheal compression at birth, if feasible. This could maximize the chance of fetal survival. Improvement of fetal short- and long-term outcomes is important.